Dinamisku grafu attēlošana - Cīpola, Kristīne (Latvijas Universitāte, 2011)
Qualification work "Graph dynamic Visualization" describes the graph dynamic and development of display tool. Tool is designed to represent the changes in graph on a timeline. This allows the user to visually create the graph, change it and create views, saving all graph changes, and fetch information on the displayed graph views of the files. The tool is created in programming languageJava. The development is fully documented, including the requirement specification, design and testing. Keywords: graphs, dynamic graphs, graph display, Java.
Dynamic graph visualization
Keywords: Datorzinātne